Estudio de mercado para la implementación de una cancha de paintball en la ciudad de Machala. - Macias Diaz, Luis David (My University, 2021)
This study aims to conduct market research in order to determine whether it is feasible to open a new paintball field with different themes to those that currently exist in the city of Machala, through quantitative research (online surveys) determining what are the most important and irrelevant factors by consumers, within this research variables related to the 4p (product, price, place and promotion) as well as the value, competition and expectations were analyzed. The data obtained in the product variable, determined that it is feasible to implement a paintball court with a Recball paintball theme (wooded areas), and that consumers want to have within the paintball court additional services such as: restaurant, bar, swimming pools, recreation center for children and sports courts, in the price variable consumers are willing to pay from $3.50 to $5. 00 and that their form of payment would be in cash, in the variable square it was found that consumers prefer the location to be in an open field, surrounded by vegetation to make the game more entertaining and eye-catching, within the variable promotion the most required by consumers is to make discounts for groups and implement a crazy day where a raffle is held and people can play for free.
El presente estudio tiene como objetivo realizar una investigación de mercado con la finalidad de conocer si es factible abrir una nueva cancha de paintball con temáticas distintas a las que existen en la actualidad en la ciudad de Machala, mediante una investigación cuantitativa (encuestas online) determinando cuales son los factores más importantes e irrelevantes por parte de los consumidores, dentro de esta investigación se analiza las variables relacionadas a las 4p (producto, precio, plaza y promoción) al igual que el valor, competencia y expectativas. Los datos obtenidos en la variable producto, determinaron que es factible implementar una cancha con una temática Recball paintball (zonas boscosas), y que los consumidores desean tener dentro de la cancha de paintball servicios adicionales como: restaurante, bar, piscinas, centro de recreación para niños y canchas deportivas, en la variable precio los consumidores están dispuesto a pagar de $3.50 a $5.00 y que su forma de pago seria en efectivo, en la variable plaza se encontró que los consumidores prefieren que la ubicación sea en un campo abierto, rodeado de vegetación para hacer el juego más entretenido y llamativo, dentro de la variable promoción la más requerida por los consumidores es realizar descuentos por grupos e implementar un día loco en donde se realice sorteo y la gente pueda jugar gratis.
Keywords: ESTUDIO DE MERCADO; MARKETING